Power system stability stability of your life - Boonchiam, Paisan (Frontiers in Engineering Innovation Research, 2007)
The electric power generation-transmission distribution grid in developed and developing countries constitutes a large system that exhibits a range of dynamic phenomena. Stability of this system needs to be maintained even when subjected to large low probability disturbances so that the electricity can be supplied to consumers with high reliability. Various control methods and controllers have been developed over time that has been used for this purpose. New technologies, however, in the area of communications and power electronics, have raised the possibility of developing much faster and more wide-area stability control that can allow safe operation of the grid closer to its limits. Tills paper presents a conceptual picture of these new stability control possibilities.